Sabuwa Pitate in the Historical Narrative of the Pioneer Pentecostal GPdI Community in Southeast Minahasa - Rokot, Ridwan Arke; Binilang, Benny B.; Rogahang, Heldy (International Journal of Education, Information Technology, and Others, 2024)
The research describes, analyzes, reflects upon, and interprets the concepts and practices of Pentecostal religiosity inspired by the philosophy of sabuwa pitate in the traditional cultural architecture of the pioneer Pentecostal GPdI community in Southeast Minahasa. Using a qualitative narrative method, data were collected through participatory observation, in-depth interviews, and documentation. Findings indicate the integration of Pentecostal teachings with Minahasa's local wisdom, the Holy Spirit experience, and worship practices emphasizing togetherness and family. This research contributes significantly to understanding and developing Pentecostal religiosity concepts and practices, constructive approaches between religious and cultural values, and elaborating the application of these values in Christian religious education and community life.